Self-reported breast and cervical cancer screening practices among women in Ghana: predictive factors and reproductive health policy implications from the WHO study on global AGEing and adult health - Martin Amogre Ayanore; Martin Adjuik; Asiwome Ameko; Nuworza Kugbey; Robert Asampong; Derrick Mensah; Robert Kaba Alhassan; Agani Afaya; Mark Aviisah; Emmanuel Manu; Francis Zotor (BMC, 2020)
Abstract Background Breast and cervical cancers constitute the two leading causes of cancer deaths among women in Ghana. This study examined breast and cervical screening practices among adult and older women in Ghana. Methods Data from a population-based cross-sectional study with a sample of 2749 women were analyzed from the study on global AGEing and adult health conducted in Ghana between 2007 and 2008. Binary and multivariable ordinal logistic regression analyses were performed to assess the association between socio-demographic factors, breast and cervical screening practices. Results We found that 12.0 and 3.4% of adult women had ever had pelvic screening and mammography respectively. Also, 12.0% of adult women had either one of the screenings while only 1.8% had both screening practices. Age, ever schooled, ethnicity, income quantile, father's education, mother's employment and chronic disease status were associated with the uptake of both screening practices. Conclusion Nationwide cancer awareness campaigns and education should target women to improve health seeking behaviours regarding cancer screening, diagnosis and treatment. Incorporating cancer screening as a benefit package under the National Health Insurance Scheme can reduce financial barriers for breast and cervical screening.